Hypertension induced by immunosuppressive drugs: a comparative analysis between sirolimus and cyclosporine - Reis, F (2009)
The purpose of this study was to compare the effects of sirolimus (SRL) vs cyclosporine (CsA) concerning the cardiovascular mechanisms hypothetically contributing to hypertension development. Three rat groups were studied: control (vehicle), CsA (5 mg/kg/d), and SRL (1 mg/kg/d). The following parameters were evaluated after 7 weeks of treatment: blood pressured (BP) and heart rate (HR; tail cuff), lipid profile, hematology, plasma and platelet 5-HT and catecholamines (HPLC-ECD), and oxidative equilibrium (serum malondialdehyde [MDA] and total antioxidant status [TAS]). Systolic (SBP) and diastolic blood pressure (DBP) values were higher (P < .001) in both the CsA (146.2 +/- 4.5 and 124.9 +/- 4.5 mm Hg) and SRL (148.9 +/- 4.8 and 126.4 +/- 6.0 mm Hg) groups vs the controls (115.9 +/- 3.3 and 99.1 +/- 2.0 mm Hg). However, HR values were elevated in CsA but not SRL animals. The dyslipidemic pattern of CsA was even more enhanced in the SRL group, with significantly higher low-density lipoprotein cholesterol (LDL-c) and triglyceride (TG) levels vs CsA (P < .05); red blood cells, hematocrit, hemoglobin concentration, mean platelet volume, and platelet distribution width were significantly (P < .05) higher in the SRL vs CsA group. The pro-oxidative profile (increased MDA/TAS) in the CsA group was not reproduced in the SRL cohort. While plasma and platelet 5-HT were elevated in SRL rats, catecholamine content was higher in CsA animals. In conclusion, this study demonstrated that CsA and SRL produce identical hypertensive effects. However, while CsA promotes oxidative stress and sympathetic activation, SRL mainly interferes with lipid profile and hematological parameters. Thus, the hypertensive effects of CsA, a calcineurin inhibitor, and of SRL, an mTOR inhibitor, are associated with impairment of distinct cardiovascular pathways